Faktor-Faktor yang Mempengaruhi Penghindaran Pajak dengan Komisaris Independen sebagai Pemoderasi - Nita Andriyani Budiman; Arina Zulfa Oktaviani; Zamrud Mirah Delima (UNIVERSITAS RAHARJA, 2024)
This study examines the impact of multinationality, tax havens, and thin capitalization on tax avoidance, with an independent commissioner acting as a moderating variable. Utilizing a purposive sampling technique, the study focuses on primary consumer goods companies listed on the Indonesia Stock Exchange from 2017 to 2021, comprising 140 observations. The analysis employs Moderated Regression Analysis (MRA) via SPSS. Findings reveal that multinationality, tax havens, and thin capitalization do not influence tax avoidance, and independent commissioners do not moderate these relationships. The implications underscore the need for a reevaluation of tax regulations and corporate governance practices within the consumer goods sector. Both companies and regulators must reassess the effectiveness of oversight mechanisms in addressing tax avoidance, emphasizing continuous monitoring and improvement in corporate governance to ensure compliance and maintain public trust. This research introduces the novelty of using independent commissioners to mediate the influence of multinationality, tax havens, and thin capitalization on tax avoidance.